Soft HRM practices, organizational commitment, work-related support and employee engagement in Bangladesh banking sector - Aktar, Alima (2018)
Although employee engagement has got a great attention among the industry practitioners in recent times, it requires more considerations particularly in the academic literature. Due to the inconclusive results of previous studies on the antecedent factors of employee engagement, this study empirically investigate the relationship between HRM practices and employee engagement among the banking employees. This study also determines whether organizational commitment can act as a mediator on HRM practices-employee engagement linkage and work-related support (i.e. supervisor, co-worker and organizational) can moderate the relationship between organizational commitment and employee engagement. The research framework of this study is developed under the norms of social exchange theory (SET). Self-administered questionnaires are distributed to the banking employees who are working in Dhaka city in Bangladesh. A total of 383 banking employees are involved in this survey study confirming a response rate of 72%. This study utilizes the partial least squares structural equation modeling (PLS-SEM) to analyze and establish the reliability and validity of measurement model and to investigate the relationships of structural model. The findings of this study show that all the HRM practices namely career advancement, employee participation, job security, performance feedback, rewards & recognition, training & development are significantly and positively related to employee engagement. Furthermore, this study also found that organizational commitment partially mediates the relationship between HRM practices and employee engagement. In addition, results of this study show that work-related support namely supervisor support and organizational support can moderate the relationship between organizational commitment and employee engagement while co-worker cannot act as a moderator. This study further discusses the theoretical contribution and managerial implications for academics and professionals. The limitations of this study are also discussed and addressed with some valuable recommendations for further research directions.